PENGARUH PEMBELAJARAN BERBASIS DIGITAL TERHADAP KEMAMPUAN AFEKTIF PESERTA DIDIK PADA MATA PELAJARAN AKIDAH AKHLAK KELAS VIII DI MTS MUHAMMADIYAH TONGKO KABUPATEN ENREKANG - Rahman, Musyirah; Fattah, Abdul; Ali Hasan, Hurriah (LPPM Universitas Islam 45, 2024)
This study aims to determine the affective abilities of students before and after digital -based learning and to find out whether there is an influence of digital -based learning on students' affective abilities on the subject of Class VIII Morals in MTs Muhammadiyah Tongko, Enrekang Regency. The purpose of this study is to improve students' affective abilities with digital -based learning. The type of research used is quantitative experimental research. The subjects of the study were the principal, the teacher of morals, and students. The research instruments used are pretest-posttest questionnaires, observation, and documentation records. The data analysis technique in the study is the normality test, heteroscedasticity test, and hypothesis test with the help of the SPSS program version 22. The results of the research obtained are the affective ability of students before digital-based learning has an average value of 117.59, and affective Ability Students after digital-based learning have an average of 124.57, and there is a significant influence between digital-based learning on student affective capabilities in the subject of morality in MTs Muhammadiyah Tongko.